Comparative analysis of human milk and infant formula derived peptides following in vitro digestion. (15th April 2017) - Su, M.-Y.; Broadhurst, M.; Liu, C.-P.; Gathercole, J.; Cheng, W.-L.; Qi, X.-Y.; Clerens, S.; Dyer, J.M.; Day, L.; Haigh, B.
Highlights: A pooled sample of 900 human milks were collected and compared to infant formula. Variations were observed in the peptide profiles between the two sample types. The differences include peptides with known biological function. Clustering of similar peptides around regions of known bioactivity was observed. Abstract: It has long been recognised that there are differences between human milk and infant formulas which lead to differences in health and nutrition for the neonate. In this study we examine and compare the peptide profile of human milk and an exemplar infant formula. The study identifies both similarities and differences in the endogenous and postdigestion peptide profiles of human milk and infant formula. This includes differences in the protein source of these peptides but also with the region within the protein producing the dominant proteins. Clustering of similar peptides around regions of high sequence identity and known bioactivity was also observed. Together the data may explain some of the functional differences between human milk and infant formula, while identifying some aspects of conserved function between bovine and human milks which contribute to the effectiveness of modern infant formula as a substitute for human milk.